Ruta hacia la correcta implementación de la gestión de activos de tecnologías de información - Aliaga Lopez, Joshep Steven II (2023)
The systems engineer at the University of Lima is prepared to detect, design, plan and solve problems in the face of constant global challenges and the global situation. Proof of this I can maintain that through my experience as a graduate I have found myself in professional situations that I have been able to face in an ideal way due to my training. The multidisciplinary approach of the career has allowed me to work in any area of negotiation, from consultant, technical implementer and technological manager, obtaining optimal results by demonstrating my professionalism and great capacity for learning and adaptation. The development of this report will detail my experience that has allowed me to achieve the role of IT manager, in order to achieve the objectives of the organization to which I belong, being able to apply my university education.